The Factor Analysis That Has Significant Influence on The Timing of Implementation of Infrastructure Development LRT (Light Rail Transit) Projects in Jabodebek - Faisal Fahmi (IPTEK The Journal of Engineering, 2017)
Jakarta Bogor Depok Light Rail Transit or abbreviated as LRT Jabodebek is a Mass Transit system with light rail (LRT) which is planned to be built in Jakarta, Indonesia and connecting Jakarta with surrounding cities like Bekasi and Bogor. One of the most important problem in the construction of this Jabodebek LRT is the delay in implementation time. This study aims to determine the factors that have a significant influence on the timing of the implementation on Jabodebek LRT. This research used descriptive method. The instruments that used in data collection is through questionnaire technique (questionnaire). This research will discuss about the application of the TOPSIS method in classifying which factors are the most significant to the time of construction on Jabodebek LRT. The weighting critriea and the classification criteria using Topsis. The results of this study indicate that land handover aspect is the first rank to be considered as the main factor causing project delay with preference value 0.9. The second aspect is the preparation of a good work plan with a preference value of 0.82. The third aspect is the selection of improper construction methods with the preference value of 0.8 and the fourth aspect which is not less important to be considered is the funding aspect of the project activity with the preference value 0.79. The author recommends that the decision makers should consider these aspects so that project implementation time can be well controlled so that there is no delay to know which factor is the most significant with respect to time in the implementation time of the project Jabodebek LRT.